Probiotics for oral health: do they deliver what they promise? - Van Holm, Wannes; Lauwens, Katalina; De Wever, Pieter; Schuermans, Art; Zayed, Naiera; Pamuk, Ferda; Saghi, Mehraveh; Fardim, Pedro; Bernaerts, Kristel; Boon, Nico; Teughels, Wim (Frontiers in Microbiology, 2023)
Probiotics have demonstrated oral health benefits by influencing the microbiome and the host. Although promising, their current use is potentially constrained by several restrictions. One such limiting factor lies in the prevailing preparation of a probiotic product. To commercialize the probiotic, a shelf stable product is achieved by temporarily inactivating the live probiotic through drying or freeze drying. Even though a lyophilized probiotic can be kept dormant for an extended period of time, their viability can be severely compromised, making their designation as probiotics questionable. Additionally, does the application of an inactive probiotic directly into the oral cavity make sense? While the dormancy may allow for survival on its way towards the gut, does it affect their capacity for oral colonisation?To evaluate this, twenty-one probiotic product for oral health were analysed for the number of viable (probiotic), culturable (CFU) and dead (postbiotic) cells, to verify whether the commercial products indeed contain what they proclaim. After isolating and uniformly lyophilizing three common probiotic species in a simple yet effective lyoprotective medium, the adhesion to saliva covered hydroxyapatite discs of lyophilized probiotics was compared to fresh or reactivated lyophilized probiotics.Unfortunately, many of the examined products failed to contain the claimed amounts of viable cells, but also the strains used were inadequately characterized and lacked clinical evidence for that unknown strain, questioning their label of a 'probiotic'. Additionally, lyophilized probiotics demonstrated low adhesive capacity compared to their counterparts, prompting the question of why fresh or reactivated probiotics are not currently used.